2009
DOI: 10.1038/nnano.2009.71
|View full text |Cite
|
Sign up to set email alerts
|

Tunable few-electron double quantum dots and Klein tunnelling in ultraclean carbon nanotubes

Abstract: Quantum dots defined in carbon nanotubes are a platform for both basic scientific studies and research into new device applications. In particular, they have unique properties that make them attractive for studying the coherent properties of single-electron spins. To perform such experiments it is necessary to confine a single electron in a quantum dot with highly tunable barriers, but disorder has prevented tunable nanotube-based quantum-dot devices from reaching the single-electron regime. Here, we use local… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(166 citation statements)
references
References 31 publications
2
158
0
3
Order By: Relevance
“…18 and 20. At the ͑11͒ side, the magnetic field splits the ͉⌽ 14, 15 11 ͘ Kramers doublet ͑that was only slightly above the ground state in Fig. 9͒ and shifts its ͉⌽ 14 ͘ component to the spectrum bottom; it is spin and isospin polarized with s = ↓ , = +.…”
Section: ↑ϯmentioning
confidence: 95%
See 2 more Smart Citations
“…18 and 20. At the ͑11͒ side, the magnetic field splits the ͉⌽ 14, 15 11 ͘ Kramers doublet ͑that was only slightly above the ground state in Fig. 9͒ and shifts its ͉⌽ 14 ͘ component to the spectrum bottom; it is spin and isospin polarized with s = ↓ , = +.…”
Section: ↑ϯmentioning
confidence: 95%
“…[10][11][12][13][14] This band gap allows for electrostatic confinement of electrons and creation of few-electron QDs, otherwise not possible due to the Klein paradox. 15 Recent experiments have shown that it is indeed possible to confine electrons in single [16][17][18][19] and double QDs ͑DQDs͒ in a CNT by means of electrostatic gates in cleanly grown small band-gap nanotubes. 5,15,20 The present study is motivated by these experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1000 nm deep trench was dry etched, leaving a thin oxide layer on top of the gates. A 5/25 nm W/Pt layer was then deposited to serve as source and drain contacts, and a single-walled carbon nanotube was grown at the last fabrication step at a temperature of 900 • C from patterned Mo/Fe catalysts [31,28]. I PC (pA)…”
Section: Methodsmentioning
confidence: 99%
“…Quantum dots allow a range of fundamental phenomena to be explored, such as the coupling of both the electron and the hole confined within a double dot, which can be controlled by applying suitable gate voltages 8 . Image reproduced from Gary Steele, Georg Gotz and Leo Kouwenhoven (cover image) 8 , © 2009 NPG.…”
Section: Join the Dotsmentioning
confidence: 99%